Economic comparison of pressure driven membrane processes to electrically driven processes for use in hydraulic fracturing. Issue 5 (24th March 2018) - Lopez, Alexander M.; Demydov, Dmytro; Rogers, Brigitte; Cleous, Haley; Tran, Long; Smith, Chase; Williams, Meaghan; Schmelzle, John; Hestekin, Jamie A.
ABSTRACT: Hydraulic fracturing has become a reliable source for oil and natural gas, yet widespread use has led to significant issues with water consumption and sustainable sourcing. Research into the reuse of produced water and flowback water have focused on mitigating water demand in this industry through membrane separation technology. In general, nanofiltration and reverse osmosis have been thought to be more economically viable for the treatment of produced and flowback water at high flowrates. However, electrodialysis and electrodeionization are generally more flexible for production of produced water and brackish water for reuse in fracturing operations when contaminant concentrations in produced water and flowback water are low. Electrodialysis and electrodeionization can also significantly reduce wastewater produced from water treatment, decreasing the amount of water that must be disposed by deep well injection. Thus, there are many cases where electrically driven processes compete well with pressure driven processes due to high water recovery and each case must be analyzed in terms of water quality variability and overall desired water treatment rate. This paper finds that at low ion concentration of inlet water, electrodialysis and electrodeionization are energy-efficient, cost-effective attractive technologies for water recovery.